Investigasi Peran Motivasi dalam Pengembangan Karir dan Kepuasan Kerja: The Investigation of Motivation Roles Amid Career Development and Job Satisfaction - Agung Nugroho Adi; Noora Fithriana (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
This study examines the role of motivation as a moderator between career development and job satisfaction. Career development is crucial to job satisfaction, and motivation is believed to strengthen this relationship. This quantitative research employed a survey involving 85 respondents from Kediri Civil Servants in 2021. To ensure the validity and reliability of the data, Confirmatory Factor Analysis was conducted using KMO and Bartlett’s tests, and reliability was tested using Cronbach’s Alpha. The classical assumption tests included the Kolmogorov-Smirnov test for normality, the Glejser test for heteroscedasticity, and the multicollinearity test. Moderation Regression Analysis was utilized to identify the types of moderators involved in the relationship between career development and job satisfaction. The findings indicate that motivation is a pure moderator, fully moderating the relationship between career development and job satisfaction. This suggests that motivation is an intervening variable and a significant determinant in enhancing job satisfaction through career development. The study provides practical implications for organizations to consider the importance of motivation in career development programs to boost employee job satisfaction. It is recommended that further research be conducted with more respondents and in various organizational contexts to obtain more comprehensive and generalizable results.